Rapid repairing material for highway and preparation method thereof

By preparing modified fibers and modified polyacrylonitrile fibers and mixing them with other materials, the problems of long construction cycles and poor weather resistance of existing road repair materials are solved, and efficient and environmentally friendly repair results are achieved.

CN119859041APending Publication Date: 2025-04-22HENAN ZHENGDA BUILDING MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510048119.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing highway repair materials are prone to shrinkage cracks during the curing process, and have poor weather resistance and durability, especially in extreme climate conditions, which are prone to aging and cracking.

Method used

A method of preparing rapid repair materials for roads is adopted. By performing specific reactions and treatments of pretreated basalt fibers, polyacrylonitrile and other materials, modified fibers and modified polyacrylonitrile fibers are prepared, and mixed with silicate cement, river sand and other materials to form repair materials with good mechanical properties and anti-aging properties.

Benefits of technology

It improves the mechanical properties and anti-aging properties of the repair material, enhances its durability and stability in extreme climates, shortens the construction cycle, and improves the repair effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005239141740000101
    Figure BDA0005239141740000101
  • Figure BDA0005239141740000111
    Figure BDA0005239141740000111
Patent Text Reader

Abstract

The invention discloses a rapid repairing material for a highway and a preparation method thereof, and relates to the technical field of pavement materials. The rapid repairing material for the highway is prepared from Portland cement, river sand, modified polyacrylonitrile fibers, a defoaming agent, a water reducing agent, modified basalt fibers, an acrylic emulsion and ammonium persulfate. The modified basalt fiber is obtained by carrying out a reaction on a pretreated basalt fiber and monohydroxy heptavinyl silsesquioxane; the modified polyacrylonitrile fiber is prepared by the following steps: reacting polyacrylonitrile with 5-azido-2-chloropyridine, spinning into fiber through wet spinning, reacting with n-butyllithium, and reacting with sodium cyanide. The rapid repairing material for the highway, prepared by the invention, has good mechanical properties, ageing resistance and antibacterial property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of pavement materials, in particular to a quick repair material for roads and a preparation method thereof. Background Art

[0002] Highways, as the arteries of the modern transportation system, will inevitably suffer various damages on their surface and internal structures during their long-term service, such as cracks, potholes, and peeling. These damages not only seriously affect the highway's traffic capacity and driving safety, but also reduce driving comfort, increase vehicle wear and tear and fuel consumption; therefore, it is particularly important to repair highways in a timely and effective manner.

[0003] Traditional highway repair materials mainly include cement concrete, asphalt mixtures, etc.; cement concrete repair materials have high strength and durability, but the construction period is long, and shrinkage cracks are easily generated during the curing process, affecting the repair effect; asphalt mixture repair materials are easy to construct and can quickly restore traffic, but their weather resistance and durability are relatively poor, especially under extreme climatic conditions, and are prone to aging, cracking and other problems.

[0004] Mechanical properties are one of the core indicators of repair materials. As a load-bearing structure, the repair materials of highways must have good mechanical properties such as compression, tension, and shear resistance to ensure that the repaired road surface can withstand vehicle loads and prevent damage from occurring again. Anti-aging performance is the key to measuring the long-term durability of repair materials. Highway repair materials must not only withstand short-term traffic loads and environmental impacts, but also face long-term natural aging processes. Ultraviolet rays, oxidation, hydrolysis and other factors can cause material performance to deteriorate or even fail. In summary, enhancing the mechanical properties and anti-aging properties of highway rapid repair materials can provide a more efficient and environmentally friendly solution for highway maintenance. Summary of the invention

[0005] The purpose of the present invention is to provide a rapid repair material for roads and a preparation method thereof, so as to solve the problems existing in the prior art.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0007] A method for preparing a quick repair material for a highway comprises the following steps:

[0008] (1) Pretreated basalt fiber, monohydroxy heptavinyl silsesquioxane, boron trifluoride etherate, and dichloromethane were mixed in a mass ratio of 1: (0.2-0.3): 0.1: (20-30), heated to 40° C. for reaction for 4 hours, filtered and washed with saturated sodium bicarbonate solution 3 times after the reaction, then washed with pure water 3 times, and vacuum dried at 50° C. to obtain modified basalt fiber;

[0009] (2) polyacrylonitrile, 5-azido-2-chloropyridine, N,N-dimethylformamide, and zinc bromide are mixed in a mass ratio of 1:(0.2-0.3):(10-12):(0.01-0.02), heated to 155-160° C. and refluxed for reaction for 20 hours, cooled to room temperature after the reaction, and dichloromethane 3-4 times the mass of N,N-dimethylformamide is added, filtered, washed with pure water for 3-4 times, and dried at 60° C. for 12-14 hours to obtain pre-modified polyacrylonitrile;

[0010] (3) using dimethyl sulfoxide to prepare a spinning solution with a mass fraction of 18% to 21% of pre-modified polyacrylonitrile, and then using a wet spinning process to eject the pre-modified polyacrylonitrile through a spinneret, enter a coagulation bath, and then wash and stretch the pre-modified polyacrylonitrile fibers, and finally collect the pre-modified polyacrylonitrile fibers on a winding roller;

[0011] (4) Pre-modified polyacrylonitrile fiber and ether are mixed in a mass ratio of 1:(40-50), cooled to -78°C using liquid nitrogen under nitrogen protection, anhydrous and oxygen-free conditions, and n-butyl lithium in an amount of 0.2-0.3 times the mass of the pre-modified polyacrylonitrile fiber is added. After stirring for 40 minutes, N,N-dimethylformamide in an amount of 4-5 times the mass of the n-butyl lithium is added, and the reaction is continued for 60 minutes. After the reaction is completed, the temperature is raised to room temperature, and a 5wt% potassium carbonate solution in an equal volume to the ether is added and stirred for 2-3 minutes. The fiber is filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14 hours to obtain polyacrylonitrile fiber.

[0012] (5) Mixing polyacrylonitrile fiber, methanol, sodium cyanide, and pure water in a mass ratio of 1:(20-30):(0.3-0.4):(2-3), heating to 80° C. and reflux reaction for 10 min. After the reaction, filtering and washing with methanol for 3-4 times, and then washing with pure water for 3-4 times, drying at 60° C. for 12-14 h, and cutting to obtain modified polyacrylonitrile fiber;

[0013] (6) Weigh the following raw materials: by mass: 100-200 parts of silicate cement, 100-150 parts of river sand, 20-30 parts of modified polyacrylonitrile fiber, 1-5 parts of defoamer, 1-10 parts of water reducer, 5-10 parts of modified basalt fiber, 50-60 parts of styrene-butadiene latex, and 1-2 parts of ammonium persulfate; mix the above raw materials evenly, add 60-80 parts of water, put into a mixer and stir for 10-30 minutes to obtain a quick repair material for roads.

[0014] As an optimization, the preparation method of the pretreated basalt fiber in step (1) is: mixing the basalt fiber and the silane coupling agent solution in a mass ratio of 1:10, ultrasonically treating at room temperature for 7 hours, filtering and washing with ethanol three times after the ultrasonic treatment, and vacuum drying to obtain the pretreated basalt fiber.

[0015] As an optimization, the preparation method of the monohydroxy heptavinyl silsesquioxane in step (1) is as follows: octavinyl silsesquioxane and trifluoromethanesulfonic acid are weighed in a molar ratio of 1:1; octavinyl silsesquioxane and dichloromethane are mixed uniformly in a mass ratio of 1:15, trifluoromethanesulfonic acid is added, and the mixture is reacted at 25°C for 4.5 hours. After the reaction is completed, the mixture is subjected to reduced pressure rotary evaporation, extracted three times with a saturated sodium bicarbonate solution, and the organic phases are combined. The organic phases are added to an acetone solution with a volume twice that of the organic phase and mixed at 25°C for 12 hours. After separation, the lower organic phase is retained, dried over anhydrous sodium sulfate, rotary evaporated, and filtered to obtain a crude product. The crude product is subjected to column chromatography to obtain monohydroxy heptavinyl silsesquioxane, wherein the column chromatography developing solvent is obtained by mixing dichloromethane and petroleum ether in a volume ratio of 1:1; and the acetone solution is obtained by mixing acetone and pure water in a volume ratio of 4:1.

[0016] As an optimization, the molecular weight of the polyacrylonitrile in step (2) is 33,000.

[0017] As an optimization, the wet spinning process parameters of step (3) are as follows: the spinneret aperture is 0.075 mm; the coagulation bath is a mixture of dimethyl sulfoxide and pure water, and the mass fraction of dimethyl sulfoxide is 70%; the coagulation bath temperature is 45°C; the drawing adopts a three-stage drawing process, the first-stage drawing temperature is 70°C, the drawing ratio is 1.5, the second-stage drawing temperature is 110°C, the drawing ratio is 4.5, and the third-stage drawing temperature is 120°C, and the drawing ratio is 1.4.

[0018] As an optimization, the length of the modified polyacrylonitrile fiber in step (5) is 12-16 mm.

[0019] As an optimization, the silicate cement in step (6) is P.O52.5; the particle size of the river sand is 1-2 mm; the defoamer is the polyether defoamer YS-001; the water reducer is the polycarboxylic acid water reducer PC-1; and the brand of the styrene-butadiene latex is SD623.

[0020] As an optimization, the basalt fiber has a length of 12 mm and a diameter of 18 μm; the silane coupling agent solution is obtained by mixing epoxybutyltrimethoxysilane and an ethanol aqueous solution, the mass fraction of epoxybutyltrimethoxysilane in the silane coupling agent solution is 2.5%, and the ethanol aqueous solution is obtained by mixing ethanol and pure water in a mass ratio of 1:1.

[0021] The present invention also provides a quick-repairing material for highway prepared by the preparation method of the quick-repairing material for highway.

[0022] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0023] The highway quick repair material prepared by the present invention comprises silicate cement, river sand, modified polyacrylonitrile fiber, defoamer, water reducer, modified basalt fiber, acrylic emulsion and ammonium persulfate; the modified basalt fiber is obtained by reacting pretreated basalt fiber and monohydroxy heptavinyl silsesquioxane; the modified polyacrylonitrile fiber is obtained by reacting polyacrylonitrile and 5-azido-2-chloropyridine, spinning into fiber by wet spinning, reacting with n-butyl lithium and then reacting with sodium cyanide.

[0024] Firstly, basalt fiber is pretreated with epoxybutyl trimethoxysilane to make the basalt fiber have epoxy groups. The epoxy groups and the hydroxyl groups on monohydroxy heptavinyl silsesquioxane undergo a ring-opening reaction, so that monohydroxy heptavinyl silsesquioxane is grafted onto the basalt fiber, thereby making the basalt have good hydrophobic properties, thereby improving the water resistance of the repair material; at the same time, a double bond structure is introduced on the surface of the basalt fiber;

[0025] Secondly, polyacrylonitrile and 5-azido-2-chloropyridine are reacted to generate a tetrazole structure with antibacterial properties, which gives the repair material good antibacterial properties. At the same time, the polyacrylonitrile is grafted with the chloropyridine structure, which is then spun into fibers by wet spinning and reacted with n-butyl lithium to convert the chlorine on the chloropyridine into an aldehyde group. The fiber undergoes a benzoin condensation reaction in the presence of sodium cyanide, and the pyridine aldehyde group is condensed to generate an enediol structure. The enediol structure has good free radical scavenging and antioxidant capabilities, which can give the repair material good anti-aging capabilities.

[0026] Finally, silicate cement, river sand, modified polyacrylonitrile fiber, defoamer, water reducer, modified basalt fiber, styrene-butadiene latex and ammonium persulfate are mixed to obtain a quick repair material for highway; short-cut basalt fiber is a rigid fiber and can well improve the strength of cement-based materials; styrene-butadiene latex can react with cement hydration products to form a macromolecular interwoven structure through ionic bonding, and this interwoven fabric can increase the density of the hardened structure. A large amount of heat will be generated during the cement hydration process, resulting in an increase in temperature. In the presence of an initiator, styrene-butadiene latex can cross-link with the double bonds on the modified basalt fiber to form a denser interwoven structure; the tetrazole and pyridine structures on the modified polyacrylonitrile fiber have good complexing ability for metal ions such as calcium, magnesium and aluminum in cement, which can further increase the density of the cross-linked network, thereby improving the mechanical properties of the repair material. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] The basalt fiber described in the following embodiments and comparative examples has a length of 12 mm and a diameter of 18 μm; the silane coupling agent solution is obtained by mixing epoxybutyltrimethoxysilane and ethanol aqueous solution, and the mass fraction of epoxybutyltrimethoxysilane in the silane coupling agent solution is 2.5%; the ethanol aqueous solution is obtained by mixing ethanol and pure water in a mass ratio of 1:1; the molecular weight of polyacrylonitrile is 33,000; the silicate cement is P.O52.5; the particle size of the river sand is 1-2 mm; the defoamer is a polyether defoamer YS-001; the water reducer is a polycarboxylic acid water reducer PC-1; and the brand of the styrene-butadiene latex is SD623.

[0029] Embodiment 1:

[0030] A method for preparing a quick repair material for a highway, the method comprising the following steps:

[0031] (1) Basalt fiber and silane coupling agent solution were mixed in a mass ratio of 1:10, and ultrasonically treated at room temperature for 7 hours. After the ultrasonic treatment, the mixture was filtered and washed three times with ethanol, and vacuum dried to obtain pretreated basalt fiber; octavinylsilsesquioxane and trifluoromethanesulfonic acid were weighed in a molar ratio of 1:1; octavinylsilsesquioxane and dichloromethane were mixed in a mass ratio of 1:15, trifluoromethanesulfonic acid was added, and the mixture was reacted at 25°C for 4.5 hours. After the reaction was completed, the mixture was subjected to reduced pressure rotary evaporation, extracted three times with saturated sodium bicarbonate solution, and the organic phases were combined. The organic phases were added to an acetone solution twice the volume of the organic phase and mixed at 25°C for 12 hours. After separation, the mixture was retained. The lower organic phase was dried over anhydrous sodium sulfate, rotary evaporated, and filtered to obtain a crude product. The crude product was subjected to column chromatography to obtain monohydroxy heptavinyl silsesquioxane. The column chromatography developing solvent was obtained by mixing dichloromethane and petroleum ether in a volume ratio of 1:1. The acetone solution was obtained by mixing acetone and pure water in a volume ratio of 4:1. The pretreated basalt fiber, monohydroxy heptavinyl silsesquioxane, boron trifluoride ether, and dichloromethane were mixed in a mass ratio of 1:0.2:0.1:20, heated to 40°C for reaction for 4h, and after the reaction was completed, filtered and washed with a saturated sodium bicarbonate solution for 3 times, then washed with pure water for 3 times, and vacuum dried at 50°C to obtain modified basalt fiber.

[0032] (2) polyacrylonitrile, 5-azido-2-chloropyridine, N,N-dimethylformamide, and zinc bromide were mixed in a mass ratio of 1:0.2:10:0.01, heated to 160°C and refluxed for 20 hours, cooled to room temperature after the reaction, and dichloromethane 3 times the mass of N,N-dimethylformamide was added, filtered, washed with pure water 4 times, and dried at 60°C for 14 hours to obtain pre-modified polyacrylonitrile;

[0033] (3) Pre-modified polyacrylonitrile is prepared into a spinning solution with a mass fraction of 18% by dimethyl sulfoxide, and the solution is ejected through a spinneret through a wet spinning process, enters a coagulation bath, and then is washed and stretched, and finally collected on a winding roller to obtain pre-modified polyacrylonitrile fiber; the wet spinning process parameters are: the spinneret aperture is 0.075 mm; the coagulation bath is a mixture of dimethyl sulfoxide and pure water, and the mass fraction of dimethyl sulfoxide is 70%; the coagulation bath temperature is 45°C; the stretching adopts a three-stage stretching process, the first-stage stretching temperature is 70°C, the stretching ratio is 1.5, the second-stage stretching temperature is 110°C, the stretching ratio is 4.5, and the third-stage stretching temperature is 120°C, and the stretching ratio is 1.4.

[0034] (4) Pre-modified polyacrylonitrile fiber and ether were mixed in a mass ratio of 1:40, cooled to -78°C using liquid nitrogen under nitrogen protection, anhydrous and oxygen-free conditions, added with n-butyl lithium in an amount of 0.2 times the mass of the pre-modified polyacrylonitrile fiber, and stirred for 40 minutes, and then added with N,N-dimethylformamide in an amount of 4 times the mass of n-butyl lithium, and continued to react for 60 minutes. After the reaction was completed, the mixture was heated to room temperature, and a 5wt% potassium carbonate solution in an equal volume to the ether was added and stirred for 3 minutes. The mixture was filtered and washed with pure water for 4 times, and dried at 60°C for 14 hours to obtain polyacrylonitrile fiber.

[0035] (5) polyacrylonitrile fiber, methanol, sodium cyanide, and pure water were mixed in a mass ratio of 1:20:0.3:2, heated to 80°C, refluxed for 10 minutes, filtered after the reaction, washed with methanol 4 times, and then washed with pure water 4 times, dried at 60°C for 14 hours, and cut to obtain modified polyacrylonitrile fiber; the length of the modified polyacrylonitrile fiber was 16 mm;

[0036] (6) Weigh the following raw materials: by mass: 100 parts of silicate cement, 100 parts of river sand, 20 parts of modified polyacrylonitrile fiber, 1 part of defoamer, 1 part of water reducer, 5 parts of modified basalt fiber, 50 parts of styrene-butadiene latex, and 1 part of ammonium persulfate; mix the above raw materials evenly, add 60 parts of water, put into a mixer and stir for 10 minutes to obtain a quick repair material for roads.

[0037] Embodiment 2:

[0038] A method for preparing a quick repair material for a highway, the method comprising the following steps:

[0039] (1) Basalt fiber and silane coupling agent solution were mixed in a mass ratio of 1:10, and ultrasonically treated at room temperature for 7 hours. After the ultrasonic treatment, the mixture was filtered and washed three times with ethanol, and vacuum dried to obtain pretreated basalt fiber; octavinylsilsesquioxane and trifluoromethanesulfonic acid were weighed in a molar ratio of 1:1; octavinylsilsesquioxane and dichloromethane were mixed in a mass ratio of 1:15, trifluoromethanesulfonic acid was added, and the mixture was reacted at 25°C for 4.5 hours. After the reaction was completed, the mixture was subjected to reduced pressure rotary evaporation, extracted three times with saturated sodium bicarbonate solution, and the organic phases were combined. The organic phases were added to an acetone solution twice the volume of the organic phase and mixed at 25°C for 12 hours. After separation, the mixture was retained. The lower organic phase was dried over anhydrous sodium sulfate, rotary evaporated, and filtered to obtain a crude product. The crude product was subjected to column chromatography to obtain monohydroxy heptavinyl silsesquioxane. The column chromatography developing solvent was obtained by mixing dichloromethane and petroleum ether in a volume ratio of 1:1. The acetone solution was obtained by mixing acetone and pure water in a volume ratio of 4:1. The pretreated basalt fiber, monohydroxy heptavinyl silsesquioxane, boron trifluoride ether, and dichloromethane were mixed in a mass ratio of 1:0.25:0.1:25, heated to 40°C for reaction for 4h, and after the reaction was completed, filtered and washed with a saturated sodium bicarbonate solution for 3 times, then washed with pure water for 3 times, and vacuum dried at 50°C to obtain modified basalt fiber.

[0040] (2) polyacrylonitrile, 5-azido-2-chloropyridine, N,N-dimethylformamide, and zinc bromide were mixed in a mass ratio of 1:0.25:11:0.015, heated to 157°C and refluxed for 20 hours, cooled to room temperature after the reaction, added with dichloromethane 3.5 times the mass of N,N-dimethylformamide, filtered, washed with pure water for 3 times, and dried at 60°C for 13 hours to obtain pre-modified polyacrylonitrile;

[0041] (3) Pre-modified polyacrylonitrile is prepared into a spinning solution with a mass fraction of 19% by dimethyl sulfoxide, and the solution is ejected through a spinneret through a wet spinning process, enters a coagulation bath, and then is washed and stretched, and finally collected on a winding roller to obtain pre-modified polyacrylonitrile fiber; the wet spinning process parameters are: the spinneret aperture is 0.075 mm; the coagulation bath is a mixture of dimethyl sulfoxide and pure water, and the mass fraction of dimethyl sulfoxide is 70%; the coagulation bath temperature is 45°C; the stretching adopts a three-stage stretching process, the first-stage stretching temperature is 70°C, the stretching ratio is 1.5, the second-stage stretching temperature is 110°C, the stretching ratio is 4.5, and the third-stage stretching temperature is 120°C, and the stretching ratio is 1.4.

[0042] (4) Pre-modified polyacrylonitrile fiber and ether were mixed in a mass ratio of 1:45, cooled to -78°C using liquid nitrogen under nitrogen protection, anhydrous and oxygen-free conditions, added with 0.25 times the mass of n-butyl lithium of the pre-modified polyacrylonitrile fiber, and continued to stir for 40 minutes, then added with 4.5 times the mass of n-butyl lithium N, N-dimethylformamide, and continued to react for 60 minutes. After the reaction was completed, the temperature was raised to room temperature, and a 5wt% potassium carbonate solution of the same volume as the ether was added and stirred for 2 minutes, filtered and washed with pure water for 3 times, and dried at 60°C for 13 hours to obtain polyacrylonitrile fiber;

[0043] (5) polyacrylonitrile fiber, methanol, sodium cyanide, and pure water were mixed in a mass ratio of 1:25:0.35:2.5, heated to 80°C and refluxed for 10 minutes, filtered and washed with methanol three times after the reaction, and then washed with pure water three times, dried at 60°C for 13 hours, and cut to obtain modified polyacrylonitrile fiber; the length of the modified polyacrylonitrile fiber was 14 mm;

[0044] (6) Weigh the following raw materials: 150 parts by mass of silicate cement, 125 parts by mass of river sand, 25 parts by mass of modified polyacrylonitrile fiber, 3 parts by mass of defoamer, 5 parts by mass of water reducer, 7 parts by mass of modified basalt fiber, 55 parts by mass of styrene-butadiene latex, and 2 parts by mass of ammonium persulfate; mix the above raw materials evenly, add 70 parts by mass of water, and stir the mixture in a mixer for 20 minutes to obtain a quick repair material for roads.

[0045] Embodiment 3:

[0046] A method for preparing a quick repair material for a highway, the method comprising the following steps:

[0047] (1) Basalt fiber and silane coupling agent solution were mixed in a mass ratio of 1:10, and ultrasonically treated at room temperature for 7 hours. After the ultrasonic treatment, the mixture was filtered and washed three times with ethanol, and vacuum dried to obtain pretreated basalt fiber; octavinylsilsesquioxane and trifluoromethanesulfonic acid were weighed in a molar ratio of 1:1; octavinylsilsesquioxane and dichloromethane were mixed in a mass ratio of 1:15, trifluoromethanesulfonic acid was added, and the mixture was reacted at 25°C for 4.5 hours. After the reaction was completed, the mixture was subjected to reduced pressure rotary evaporation, extracted three times with saturated sodium bicarbonate solution, and the organic phases were combined. The organic phases were added to an acetone solution twice the volume of the organic phase and mixed at 25°C for 12 hours. After separation, the mixture was retained. The lower organic phase was dried over anhydrous sodium sulfate, rotary evaporated, and filtered to obtain a crude product. The crude product was subjected to column chromatography to obtain monohydroxy heptavinyl silsesquioxane. The column chromatography developing solvent was obtained by mixing dichloromethane and petroleum ether in a volume ratio of 1:1. The acetone solution was obtained by mixing acetone and pure water in a volume ratio of 4:1. The pretreated basalt fiber, monohydroxy heptavinyl silsesquioxane, boron trifluoride ether, and dichloromethane were mixed in a mass ratio of 1:0.3:0.1:30, heated to 40°C for reaction for 4h, filtered, washed with a saturated sodium bicarbonate solution for 3 times, then washed with pure water for 3 times, and vacuum dried at 50°C to obtain modified basalt fiber.

[0048] (2) polyacrylonitrile, 5-azido-2-chloropyridine, N,N-dimethylformamide, and zinc bromide were mixed in a mass ratio of 1:0.3:12:0.02, heated to 155°C and refluxed for 20 hours, cooled to room temperature after the reaction, added with dichloromethane 4 times the mass of N,N-dimethylformamide, filtered, washed with pure water 3 times, and dried at 60°C for 12 hours to obtain pre-modified polyacrylonitrile;

[0049] (3) Pre-modified polyacrylonitrile is prepared into a spinning solution with a mass fraction of 21% by using dimethyl sulfoxide, and the solution is ejected through a spinneret through a wet spinning process, enters a coagulation bath, and then is washed and stretched, and finally collected on a winding roller to obtain pre-modified polyacrylonitrile fiber; the wet spinning process parameters are: the spinneret aperture is 0.075 mm; the coagulation bath is a mixture of dimethyl sulfoxide and pure water, and the mass fraction of dimethyl sulfoxide is 70%; the coagulation bath temperature is 45°C; the stretching adopts a three-stage stretching process, the first-stage stretching temperature is 70°C, the stretching ratio is 1.5, the second-stage stretching temperature is 110°C, the stretching ratio is 4.5, and the third-stage stretching temperature is 120°C, and the stretching ratio is 1.4.

[0050] (4) Pre-modified polyacrylonitrile fiber and ether were mixed in a mass ratio of 1:50, cooled to -78°C using liquid nitrogen under nitrogen protection, anhydrous and oxygen-free conditions, added with n-butyl lithium in an amount of 0.3 times the mass of the pre-modified polyacrylonitrile fiber, and stirred for 40 minutes, and then added with N,N-dimethylformamide in an amount of 5 times the mass of the n-butyl lithium, and continued to react for 60 minutes. After the reaction was completed, the mixture was heated to room temperature, and a 5wt% potassium carbonate solution in an equal volume to the ether was added and stirred for 2 minutes, filtered, washed with pure water for 3 times, and dried at 60°C for 12 hours to obtain polyacrylonitrile fiber;

[0051] (5) polyacrylonitrile fiber, methanol, sodium cyanide, and pure water were mixed in a mass ratio of 1:30:0.4:3, heated to 80°C, refluxed for 10 minutes, filtered after the reaction, washed with methanol three times, and then washed with pure water three times, dried at 60°C for 12 hours, and cut to obtain modified polyacrylonitrile fiber; the length of the modified polyacrylonitrile fiber was 12 mm;

[0052] (6) Weigh the following raw materials: 200 parts by mass of silicate cement, 150 parts by mass of river sand, 30 parts by mass of modified polyacrylonitrile fiber, 5 parts by mass of defoamer, 10 parts by mass of water reducer, 10 parts by mass of modified basalt fiber, 60 parts by mass of styrene-butadiene latex, and 2 parts by mass of ammonium persulfate; mix the above raw materials evenly, add 80 parts by mass of water, and stir the mixture in a mixer for 10 minutes to obtain a quick repair material for roads.

[0053] Comparative Example 1:

[0054] The preparation method of the highway rapid repair material of Comparative Example 1 is different from that of Example 2 in that the modified basalt fiber is not contained.

[0055] Comparative Example 2:

[0056] The preparation method of the highway rapid repair material of Comparative Example 2 is different from that of Example 2 in that modified polyacrylonitrile fiber is not contained.

[0057] Comparative Example 3:

[0058] The preparation method of the highway rapid repair material of Comparative Example 3 differs from that of Example 2 in that step (4) is not included, and step (3) is modified as follows: pre-modified polyacrylonitrile is prepared into a spinning solution with a mass fraction of 21% by using dimethyl sulfoxide, and the solution is ejected through a spinneret through a wet spinning process, enters a coagulation bath, and then washed and stretched, and finally collected on a winding roller to obtain modified polyacrylonitrile fiber; the wet spinning process parameters are as follows: the spinneret aperture is 0.075 mm; the coagulation bath is a mixture of dimethyl sulfoxide and pure water, and the mass fraction of dimethyl sulfoxide is 70%; the coagulation bath temperature is 45°C; the stretching adopts a three-stage stretching process, the first-stage stretching temperature is 70°C, the stretching multiple is 1.5, the second-stage stretching temperature is 110°C, the stretching multiple is 4.5, and the third-stage stretching temperature is 120°C, and the stretching multiple is 1.4.

[0059] The repair materials prepared in the above embodiments and comparative examples were cured and then tested. The curing conditions were a curing temperature of 20° C., a humidity of 98%, and a curing time of 28 days.

[0060] Test Example 1:

[0061] Mechanical properties test:

[0062] Test method: According to the standard GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", all the repair materials prepared in the comparative examples and embodiments were made into standard test blocks, and the compressive strength was tested. The results are shown in Table 1.

[0063] Test of anti-aging performance: According to the standard GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", all the repair materials obtained in the comparative examples and embodiments were made into standard test blocks, and the test blocks were placed in a UV aging box for strong UV radiation, wherein the conditions of strong UV radiation are: light intensity of 1160W / m, temperature of 80°C, and light exposure time of 240h. After the light exposure, the compressive strength was tested according to the test method of mechanical properties, and the compressive strength retention rate was calculated. The results are shown in Table 1.

[0064] Table 1

[0065]

[0066]

[0067] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the highway rapid repair material prepared by the present invention has good mechanical properties and anti-aging properties.

[0068] By comparison, the compressive strength of Examples 1 to 3 is greater than that of Comparative Examples 1 to 2, and the compressive strength retention rate of Examples 1 to 3 is greater than that of Comparative Examples 2 to 3; it indicates that after the reaction of polyacrylonitrile and 5-azido-2-chloropyridine, the polyacrylonitrile is grafted with the chloropyridine structure, and then the fiber is spun into fiber by wet spinning and then reacted with n-butyl lithium to convert the chlorine on the chloropyridine into an aldehyde group, and the fiber undergoes a benzoin condensation reaction in the presence of sodium cyanide, and the pyridine aldehyde group is condensed to generate an enediol structure, which has good free radical scavenging and antioxidant capabilities, and can give the repair material good anti-aging capabilities; silicate cement, river sand, modified polyacrylonitrile fiber, defoamer, water reducer, modified basalt fiber, Styrene butadiene latex and ammonium persulfate are mixed to obtain a quick repair material for roads; short-cut basalt fibers are rigid fibers that can greatly improve the strength of cement-based materials; styrene butadiene latex can react with cement hydration products to form a macromolecular interwoven structure through ionic bonding, and this interwoven structure can increase the density of the hardened structure. A large amount of heat will be generated during the cement hydration process, causing the temperature to rise. In the presence of an initiator, styrene butadiene latex can cross-link with the double bonds on the modified basalt fibers to form a denser interwoven structure; the tetrazole and pyridine structures on the modified polyacrylonitrile fibers have good complexing ability for metal ions such as calcium, magnesium, and aluminum in cement, which can further increase the density of the cross-linked network, thereby improving the mechanical properties of the repair material.

[0069] Test Example 2:

[0070] Antibacterial performance test:

[0071] Test method: The repair materials prepared in the examples and comparative examples were crushed, and then filtered using a 0.08 nm standard sieve to obtain powder with a particle size of less than 0.08 nm. 2 g of the powder was placed on a filter paper with a diameter of 1 cm, and the filter paper was placed in a solid culture medium smeared with bacterial liquid, and cultured at 37°C for 12 hours. The bacterial species was Staphylococcus aureus, and the size of the inhibition zone was determined using the Oxford cup method. The results are shown in Table 2.

[0072] Table 2

[0073] Diameter of antibacterial ring (mm) Diameter of antibacterial ring (mm) Example 1 17.5 Comparative Example 1 17.3 Example 2 17.6 Comparative Example 2 12.3 Example 3 17.9 Comparative Example 3 17.1

[0074] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 2, it can be found that the highway rapid repair material prepared by the present invention has good antibacterial properties.

[0075] By comparison, the antibacterial rates of Examples 1 to 3 are greater than that of Comparative Example 2, indicating that firstly, epoxybutyltrimethoxysilane is used to pretreat the basalt fiber so that the basalt fiber has an epoxy group, and the epoxy group and the hydroxyl group on the monohydroxyl heptavinyl silsesquioxane undergo a ring-opening reaction so that the monohydroxyl heptavinyl silsesquioxane is grafted onto the basalt fiber, so that the basalt has good hydrophobic properties, thereby improving the water resistance of the repair material; secondly, after polyacrylonitrile and 5-azido-2-chloropyridine are reacted, a tetrazole structure with antibacterial properties is generated, which gives the repair material good antibacterial properties.

[0076] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a rapid repair material for a highway, characterized in that: The method comprises the following preparation steps: (1) Pretreated basalt fiber, monohydroxy heptavinyl silsesquioxane, boron trifluoride etherate, and dichloromethane were mixed in a mass ratio of 1: (0.2-0.3): 0.1: (20-30), heated to 40° C. for reaction for 4 hours, filtered and washed with saturated sodium bicarbonate solution 3 times after the reaction, then washed with pure water 3 times, and vacuum dried at 50° C. to obtain modified basalt fiber; (2) polyacrylonitrile, 5-azido-2-chloropyridine, N,N-dimethylformamide, and zinc bromide are mixed in a mass ratio of 1:(0.2-0.3):(10-12):(0.01-0.02), heated to 155-160° C. and refluxed for reaction for 20 hours, cooled to room temperature after the reaction, and dichloromethane 3-4 times the mass of N,N-dimethylformamide is added, filtered, washed with pure water for 3-4 times, and dried at 60° C. for 12-14 hours to obtain pre-modified polyacrylonitrile; (3) using dimethyl sulfoxide to prepare a spinning solution with a mass fraction of 18% to 21% of pre-modified polyacrylonitrile, and then using a wet spinning process to eject the pre-modified polyacrylonitrile through a spinneret, enter a coagulation bath, and then wash and stretch the pre-modified polyacrylonitrile fibers, and finally collect the pre-modified polyacrylonitrile fibers on a winding roller; (4) Pre-modified polyacrylonitrile fiber and ether are mixed in a mass ratio of 1:(40-50), cooled to -78°C using liquid nitrogen under nitrogen protection, anhydrous and oxygen-free conditions, and n-butyl lithium in an amount of 0.2-0.3 times the mass of the pre-modified polyacrylonitrile fiber is added. After stirring for 40 minutes, N,N-dimethylformamide in an amount of 4-5 times the mass of the n-butyl lithium is added, and the reaction is continued for 60 minutes. After the reaction is completed, the temperature is raised to room temperature, and a 5wt% potassium carbonate solution in an equal volume to the ether is added and stirred for 2-3 minutes. The fiber is filtered and washed with pure water for 3-4 times, and dried at 60°C for 12-14 hours to obtain polyacrylonitrile fiber. (5) Mixing polyacrylonitrile fiber, methanol, sodium cyanide, and pure water in a mass ratio of 1:(20-30):(0.3-0.4):(2-3), heating to 80° C. and reflux reaction for 10 min. After the reaction, filtering and washing with methanol for 3-4 times, and then washing with pure water for 3-4 times, drying at 60° C. for 12-14 h, and cutting to obtain modified polyacrylonitrile fiber; (6) Weigh the following raw materials: by mass: 100-200 parts of silicate cement, 100-150 parts of river sand, 20-30 parts of modified polyacrylonitrile fiber, 1-5 parts of defoamer, 1-10 parts of water reducer, 5-10 parts of modified basalt fiber, 50-60 parts of styrene-butadiene latex, and 1-2 parts of ammonium persulfate; mix the above raw materials evenly, add 60-80 parts of water, put into a mixer and stir for 10-30 minutes to obtain a quick repair material for roads.

2. The method for preparing a rapid repair material for highway according to claim 1, characterized in that: The preparation method of the pretreated basalt fiber in step (1) is as follows: basalt fiber and silane coupling agent solution are mixed in a mass ratio of 1:10, ultrasonically treated at room temperature for 7 hours, filtered and washed three times with ethanol after the ultrasonic treatment, and vacuum dried to obtain the pretreated basalt fiber.

3. The method for preparing a rapid repair material for highway according to claim 1, characterized in that: The preparation method of the monohydroxy heptavinyl silsesquioxane in step (1) is as follows: octavinyl silsesquioxane and trifluoromethanesulfonic acid are weighed in a molar ratio of 1:1; octavinyl silsesquioxane and dichloromethane are mixed uniformly in a mass ratio of 1:15, trifluoromethanesulfonic acid is added, and the mixture is reacted at 25°C for 4.5 hours. After the reaction is completed, the mixture is subjected to reduced pressure rotary evaporation, extracted three times with a saturated sodium bicarbonate solution, and the organic phases are combined. The organic phases are added to an acetone solution with a volume twice that of the organic phase and mixed at 25°C for 12 hours. After separation, the lower organic phase is retained, dried over anhydrous sodium sulfate, rotary evaporated, and filtered to obtain a crude product. The crude product is subjected to column chromatography to obtain monohydroxy heptavinyl silsesquioxane, wherein the column chromatography developing solvent is obtained by mixing dichloromethane and petroleum ether in a volume ratio of 1:1; and the acetone solution is obtained by mixing acetone and pure water in a volume ratio of 4:

1.

4. The method for preparing a rapid repair material for highway according to claim 1, characterized in that: The molecular weight of the polyacrylonitrile in step (2) is 33,000.

5. The method for preparing a rapid repair material for highway according to claim 1, characterized in that: The wet spinning process parameters of step (3) are as follows: the spinneret aperture is 0.075 mm; the coagulation bath is a mixture of dimethyl sulfoxide and pure water, and the mass fraction of dimethyl sulfoxide is 70%; the coagulation bath temperature is 45°C; the drawing adopts a three-stage drawing process, the first-stage drawing temperature is 70°C, the drawing ratio is 1.5, the second-stage drawing temperature is 110°C, the drawing ratio is 4.5, and the third-stage drawing temperature is 120°C, and the drawing ratio is 1.

4.

6. The method for preparing a rapid repair material for highway according to claim 1, characterized in that: The length of the modified polyacrylonitrile fiber in step (5) is 12-16 mm.

7. The method for preparing a rapid repair material for highway according to claim 1, characterized in that: In step (6), the silicate cement is P.O52.5; the river sand particle size is 1-2 mm; the defoamer is polyether defoamer YS-001; the water reducer is polycarboxylic acid water reducer PC-1; and the brand of styrene-butadiene latex is SD623.

8. The method for preparing a rapid repair material for highway according to claim 2, characterized in that: The basalt fiber has a length of 12 mm and a diameter of 18 μm; the silane coupling agent solution is obtained by mixing epoxybutyltrimethoxysilane and ethanol aqueous solution, the mass fraction of epoxybutyltrimethoxysilane in the silane coupling agent solution is 2.5%, and the ethanol aqueous solution is obtained by mixing ethanol and pure water in a mass ratio of 1:

1.

9. A rapid repair material for highway prepared according to the method for preparing the rapid repair material for highway according to any one of claims 1 to 8.